Iodocarbamation of N‐Homopropargyl Carbamates: Mild and Stereoselective Entry to Functionalized Oxazinan‐2‐ones. Issue 18 (12th May 2017) - Quinodoz, Pierre; Quelhas, Alexandre; Wright, Karen; Drouillat, Bruno; Marrot, Jérôme; Couty, François
Abstract : An efficient and general iodocarbamation of benzyl N ‐homopropargylcarbamates has been developed by using iodine as the electrophilic agent. This regio‐ and stereoselective cyclization yielded ( E )‐6‐iodomethyleneoxazinan‐2‐ones, which can be further transformed through palladium cross‐coupling reactions followed by hydrogenation to produce 1, 3‐oxazinan‐2‐ones. Abstract : The iodocarbamation of N ‐Cbz‐homopropargylamines gives high yields of stereodefined 6‐iodomethyleneoxazin‐2‐ones that can be further transformed into oxazinan‐2‐ones.